Edukasi Pencegahan dan Terapi Farmakologi Asma Selama Kehamilan di Puskesmas Sidotopo Wetan Surabaya - Ninik Mas Ulfa; Rizky Darmawan (STIE Malangkucecwara, 2022)
Asthma is a chronic disease of the respiratory tract characterized by inflammation, causing clinical symptoms in the form of episodic wheezing, coughing, and shortness of breath in the chest. Research proves that asthma in pregnancy has a negative impact during the pregnancy process. Pregnancy with asthma is a health problem whose prevalence is estimated to increase. The prevalence of asthma in 1997-2001 ranged from 3.7-8.4% in pregnant women in the United States and respiratory disorders are very common in pregnant women. The importance of up-to-date information on pregnant women is very necessary so that the mortality rate decreases due to asthma during pregnancy, so it is necessary to carry out this community service with the aim of providing information about asthma education and knowledge during pregnancy, its prevention and pharmacological therapy. The targets of this community service are pregnant women and cadres of the Sidotopo Wetan Health Center Surabaya. The results showed that from the participants who attended the counseling, providing data that had been carried out descriptive analysis that knowledge increased well (76%-100%) as many as 28 participants (100%), meaning that participants' knowledge increased after being given counseling with a significance of = 0.00 ( < 0.05). These results indicate that the provision of counseling is very effective in increasing knowledge. bstract contains the main issues, goals of service, methods, results and implications